Lack of correlation of BTNL2 polymorphism and cancer risk in sarcoidosis. BTNL2 and cancer risk in sarcoidosis - gaillot-drevon, maud; Calender, alain; Blay, jean yves; Valeyre, dominique; Israel-Biet, dominique; Roy, pascal; Pacheco, yves (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: Sarcoidosis is a polygenic immune disorder disease with predominant manifestations in the lung. BTNL2 gene polymorphisms were previously linked to susceptibility to sarcoidosis. Relationships between sarcoidosis and cancers have been suspected for a long time but little evidence has been reported until now, and recent works show a link between butyrophilin family proteins and anti tumor immunity. Methods: We studied the polymorphism of the rs2076530 SNP of BTNL2 gene in 35 patients with sarcoidosis and cancer compared to 340 sarcoidosis without cancer, 271 controls and 32 cancer matched controls. Results: We found no association between BTNL2 genotype and cancer risk in sarcoidosis (OR: 2,34; CI95%: 1,30 – 4,20; p = 0,15). Sarcoidosis is associated with the rs2076530SNP of BTNL2 gene. The AA genotype is significantly associated with a 3 more increased risk of sarcoidosis compared to the GG genotype in a co-dominant model (OR: 3,22; CI95%: 2,58 – 4,06; p < 0.0001). The AG genotype is associated with a 1,8 more increased risk (OR: 1,79; CI95%: 1,42 – 2,26). Conclusions: These results confirm the association of BTNL2 rs2076530SNP with the susceptibility to develop sarcoidosis, but not with an increased risk of cancer in these patients.